Modern Cybersecurity Technology Adoption in Nepal - Bhattarai, Sijan (NPRC Journal of Multidisciplinary Research, 2026)
Background: Rapid growth in internet connectivity, digital banking, and online services has accelerated Nepal’s digital transformation in recent years. While this expansion has improved financial inclusion and service delivery, it has also exposed critical vulnerabilities in national cyber infrastructure. Increasing cybercrime incidents, weak cybersecurity awareness, and limited technical capacity have made cybersecurity a growing national concern, particularly for banking, government, and business sectors. Methods: This study employed a descriptive and analytical design with a case-based exploratory approach to examine cybersecurity technology adoption in Nepal across SOC, offensive security, and GRC domains. Primary data were collected through structured interviews with senior and mid-level engineers from cybersecurity companies via email, LinkedIn, and in-person or virtual meetings. Discussions focused on tools, technologies, operational practices, and implementation challenges. Secondary data were obtained from government reports, academic literature, regulatory publications, and global cybersecurity indices to contextualize cyber threats and policy frameworks. Access to detailed technical information was limited due to confidentiality and organizational policies; findings reflect high-level insights validated with company representatives. Data were analyzed descriptively and comparatively to identify common patterns, technological trends, and gaps in cybersecurity adoption across organizations. Results: Nepal has made measurable progress in foundational cybersecurity, ranking Tier 3 in the Global Cybersecurity Index 2024. Common threats include phishing, ransomware, malware, social engineering, and web application exploitation, fueled by weak system configurations, low user awareness, and limited law enforcement. Leading firms are adopting technologies like SIEM monitoring, anomaly detection, network analysis, vulnerability assessments, penetration testing, endpoint security, and compliance frameworks (PCI DSS, ISO). Adoption remains uneven due to skill shortages, funding constraints, and policy gaps. Conclusion: Nepal’s cybersecurity is evolving but still unprepared for advanced threats. Strengthening coordination, developing skilled workforce, deploying automated solutions, and enforcing cyber policies are essential. Context-specific, scalable strategies are key to enhancing the country’s digital resilience. Novelty: This study provides a consolidated analysis of cybersecurity threats, technologies challenges, and policy initiatives in Nepal while presenting real-world insights from domestic cybersecurity companies offering understanding of Nepal’s current cyber readiness.